A Metamaterial Loaded High Gain Low Profile RHCP Microstrip Antenna for X-Band Applications - Kumar Shrivastava M.; Singh R.; Samantaray D.; Khan A.; Kumar Gautam A.; Kumar Singh A. (My University, 2025)
This paper presents the design of a right-hand circularly polarized (RHCP) microstrip antenna loaded with metamaterial to achieve high-gain performance. The metamaterial (MTM), a 5 × 5 array of unit cells with a negative refractive index, is designed on one-sided FR4 dielectric material with dimensions 0.79 λ0 × 0.79λ{0 × 0.023λ0 , where λ0 is the free-space wavelength at 8.76 GHz. Both the antenna and the unit cells are designed on an FR4 substrate with a loss tangent of 0.02 and relative permittivity of 4.4. The antenna and MTM maintain the same area, with an air gap of 1 mm between them. The overall structure achieves a gain of 8.1 dBic at 9.5 GHz with stacking, compared to 4.4 dBic without the MTM stacking. The measured bandwidth of the proposed antenna is 1.98 GHz (8.76-10.74 GHz), which falls within the lower X-band, making it suitable for both military and maritime radar applications. © 2013 IEEE.